Synthesis and Characterization of Oxidovanadium(IV) Complexes of 2-((E)-(6-Fluorobenzo[d]thiazol-2-ylimino)methyl)-6-methoxyphenol and Their Antimicrobial, Antioxidant, and DNA-Binding Studies - K. Savithri; H. D. Revanasiddappa (Bioinorganic Chemistry and Applications)
Two novel oxidovanadium(IV) complexes with a new bidentate (O- and N-) imine-based ligand 2-((E)-(6-fluorobenzo[d]thiazol-2-ylimino)methyl)-6-methoxyphenol (HL) were synthesized under in situ experimental condition where VOSO4 acts as a kinetic template in the ratio 2 : 1 (L : M) and mixed ligand complex using 1,10-phenanthroline (phen) in 1 : 1 : 1 (L : M : phen) ratio. The synthesized compounds were structurally characterized by microanalysis, magnetic susceptibility, FTIR, electronic spectra, TG/DTA, ESR, and molar conductance studies. Based on the spectral studies, the complexes have the general composition [VO(L)2] (C1) and [VO(L)phen] (C2) in a square pyramid geometrical fashion. The synthesized compounds were primarily screened for their in vitro growth inhibiting activity against different strains of bacteria, namely, E. coli, B. subtilis, S. aureus, and P. aeruginosa by the disc diffusion method. Also, the antifungal activity was determined against C. albicans and A. niger by the Bateman poisoned technique. The in vitro antioxidant activity of all the compounds was determined by DPPH free radical-scavenging assay. Intercalative mode of DNA-binding properties of the oxidovanadium(IV) complexes with calf-thymus DNA (CT-DNA) was investigated using UV, fluorescence spectra, and viscosity measurements.